2014
DOI: 10.1186/ar4520
|View full text |Cite
|
Sign up to set email alerts
|

Umbilical cord mesenchymal stem cell transplantation in active and refractory systemic lupus erythematosus: a multicenter clinical study

Abstract: IntroductionIn our present single-center pilot study, umbilical cord (UC)–derived mesenchymal stem cells (MSCs) had a good safety profile and therapeutic effect in severe and refractory systemic lupus erythematosus (SLE). The present multicenter clinical trial was undertaken to assess the safety and efficacy of allogeneic UC MSC transplantation (MSCT) in patients with active and refractory SLE.MethodsForty patients with active SLE were recruited from four clinical centers in China. Allogeneic UC MSCs were infu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
183
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 259 publications
(190 citation statements)
references
References 46 publications
3
183
0
4
Order By: Relevance
“…In this context, a GMP-compliant method was PL as a substitute for FBS. While other isolation and expansion protocols of UC-MSCs were proposed [33,35], the method we adopted allows a minimal manipulation of the UC, thus avoiding the possible initial selection of cell subpopulations [6] yielding the isolation of high-grade MSCs [36].…”
Section: Discussionmentioning
confidence: 99%
“…In this context, a GMP-compliant method was PL as a substitute for FBS. While other isolation and expansion protocols of UC-MSCs were proposed [33,35], the method we adopted allows a minimal manipulation of the UC, thus avoiding the possible initial selection of cell subpopulations [6] yielding the isolation of high-grade MSCs [36].…”
Section: Discussionmentioning
confidence: 99%
“…The eligibility criteria included treatment-refractory and active disease, as well as a Systemic Lupus Erythematosus Disease Activity Index (SLEDAI) score of more than eight or at least one British Isles Lupus Assessment Group (BILAG) grade A or at least two BILAG grade B manifestations. Refractory treatment meant lack of response to treatment with monthly intravenous pulse cyclophosphamide (CYC, 500-750 mg/ m 2 ) for C6 months or lack of response to treatment with oral mycophenolate mofetil (MMF, C1000 mg/day) or leflunomide (20 mg/day) for C3 months, or continued daily doses of C20 mg of prednisone or its equivalent [15,16]. Patients were excluded from the study if they had the following conditions: (1) infection: including pneumonia, pulmonary tuberculosis, hepatitis, skin infection, central nervous system infection; (2) heart failure: New York Heart Association functional classification III or IV;…”
Section: Patients' Enrollmentmentioning
confidence: 99%
“…In that study, the authors examined several published studies which used MSC from various sources and demonstrated efficacy [4]. A more recent evaluation completed in 2014 demonstrated that umbilical cord derived MSC resulted in satisfactory clinical response but the response was time limited to approximately 6 months [5]. MSC therapy has the advantages of modulating the inflammatory cascade while stabilizing the progenitor cell lines thereby reducing the inflammatory and autoimmune dysfunction.…”
Section: Introductionmentioning
confidence: 99%